PENGARUH MINAT BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI MA PONDOK PESANTREN SE-KECAMATAN KAMPAR TIMUR - Heri Rahman; Gimin Gimin; Gusnardi Gusnardi (PEKBIS, 2018)
This research was aimed: (1) to find out the effect of the school environment towardthe students’ learning interest at all islamic senior high school of Kampar Timur; (2)to find out the effect of the students’ learning interest toward the students’ learningachievement at all islamic senior high school of Kampar Timur; (3) to find out theeffect of the school environment toward the the students’ learning achievement at allislamic senior high school of Kampar Timur; (4) to find out the effect of the schoolenvironment toward the students’ learning achievement through the students’learning interest at all islamic senior high school of Kampar Timur. Population of thisresearch was 114 students of all islamic senior high school of Kampar Timur.Sample of this research was all of the total number of population namely 114students, the technique to determine the sample used sampling jenuh. Technique tocollect the data used questioner data and documentation. Based on the dataanalysis, the writer found that (1) there was no a significant effect of the schoolenvironment toward the students’ learning interest at all islamic senior high school ofKampar Timur; (2) there was a significant effect of the students’ learning interesttoward the students’ learning achievement; (3) there was a significant effect of theschool environment toward the students’ learning achievement at all islamic seniorhigh school of Kampar Timur; (4) there was no a significant effect of the schoolenvironment toward the students’ learning achievement through the students’learning interest at all islamic senior high school of Kampar Timur.